2017
DOI: 10.23917/komuniti.v8i5.2942
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Komunikasi Guru Terhadap Motivasi Belajar Siswa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 3 publications
1
6
0
4
Order By: Relevance
“…The results of this study support research conducted by Sucia (2017) stated that there is a positive and significant influence of teacher communication on student motivation. Sutardi (2016) revealed that there was a positive and significant influence between teacher competencies on learning outcomes.…”
Section: The Effect Of Teacher Teaching Methods On Students' Learningsupporting
confidence: 88%
“…The results of this study support research conducted by Sucia (2017) stated that there is a positive and significant influence of teacher communication on student motivation. Sutardi (2016) revealed that there was a positive and significant influence between teacher competencies on learning outcomes.…”
Section: The Effect Of Teacher Teaching Methods On Students' Learningsupporting
confidence: 88%
“…In order that the students can learn well, the methods of teaching shoud be made as attractive as possible. Furthermore Sucia (2017), explains that the pleasure created by the teachers makes the students feel happy about the subjects given. Something positive can increase student motivation and increase student enthusiasm for learning.…”
Section: Fun In Learning Sciencementioning
confidence: 99%
“…karena faktor utama yang berdampak pada keaktifan siswa dalam mengikuti proses belajar mengajar. Hal ini senada dengan penelitian yang dilakukan oleh Sucia (2016) yang meyatakan bahwa di dalam proses pembelajaran terdapat hubungan antara siswa dengan guru, hubungan yang baik antara siswa dan guru mendorong terciptanya pembelajaran yang maksimal. Siswa lebih termotivasi dalam belajar dengan guru yang perhatian, penyabar, dan dekat dengan siswa.…”
Section: Pembahasanunclassified